Analisis Profil Kekuatan dan Daya Tahan Otot Lengan serta Otot Perut Siswa Kelas III Sekolah Dasar Melalui Item Terpilih TKJI sebagai Refleksi Pembelajaran PJOK dalam Program PPG - Dito Alfian, Irfan; Alfan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical fitness is an important component in supporting physical development and the success of Physical Education, Sports, and Health (PJOK) learning in elementary schools. Information regarding the profile of arm muscle strength and abdominal muscle endurance among elementary school students is needed as a basis for learning evaluation and reflection within the Teacher Professional Education Program (PPG). This study aimed to analyze the profile of arm muscle strength and abdominal muscle endurance of third-grade elementary school students using selected items from the Indonesian Physical Fitness Test (TKJI). This research employed a quantitative approach with a descriptive survey method. The participants consisted of 28 third-grade students of SDN Percobaan 1 Malang City selected through a total sampling technique. The research instruments were selected TKJI items, namely the flexed-arm hang test to measure arm muscle strength and endurance and the sit-up test to measure abdominal muscle endurance. Data were analyzed using descriptive statistics through percentage calculations and categorization of test results. The findings indicated that the students’ physical fitness profile generally ranged from good to moderate categories. The distribution of results showed that 24.14% of students were in the very good category, 36.21% in the good category, 29.31% in the moderate category, and 10.34% in the poor category, while no students were classified in the very poor category. In the sit-up test, 34.48% of students were categorized as very good, 48.28% as good, 13.79% as moderate, and 3.45% as poor. Meanwhile, in the flexed-arm hang test, 13.79% of students were categorized as very good, 24.14% as good, 44.83% as moderate, and 17.24% as poor. These findings indicate that abdominal muscle endurance was better developed than arm muscle strength. Therefore, physical fitness assessment results can be utilized as a basis for pedagogical reflection in designing PJOK learning activities that are more responsive to students’ needs within the Teacher Professional Education Program (PPG).